Disparities in Reperfusion Therapy and Time Delays Among Patients With Ischemic Stroke and a History of Mental Illness. Issue 11 (18th August 2022) - Mackenhauer, Julie; Frischknecht Christensen, Erika; Andersen, Grethe; Mainz, Jan; Johnsen, Søren Paaske
Abstract : Background: Comorbid mental illness may delay recognition of stroke symptoms and reduce the chance of reperfusion therapy. The aim of this study was to compare the use of reperfusion therapy and treatment delays in patients with or without a history of mental illness. Methods: A nationwide registry-based cohort study of patients with ischemic stroke. We combined data from the Danish Stroke Registry and the Danish Quality Database for Prehospital Emergency Medical Services from 2016 to 2017 containing information on reperfusion therapy (thrombolysis or thrombectomy) and relevant time stamps. Patients were categorized according to the severity of their mental health history (how recent and severity, for example, hospital- versus primary-based care). Results: A total of 19 592 admissions were included (18% had a minor, 3% had a moderate, and 3% had a history of major mental illness). Significant differences were found regarding age, comorbidity, and socioeconomic factors. Reperfusion therapy was used in 17% of patients. Patients: with a history of mental illness were less likely to receive reperfusion therapy: risk ratios with 95% CI were 0.79 (0.72–0.86) for minor, 0.85 (0.72–0.99) for moderate, and 0.63 (0.51–0.77) for patients with a history major mental illness, respectively. Total prehospital delay was longer for patients with a history of major mental illness compared to patients with no history of mental illness, especially when no call had been made to the emergency medical service. The median times from symptom onset to hospital arrival was 811 minutes (197–2845) and 115 minutes (41–188), respectively. We found no differences regarding door-to-needle time, response time, on-scene time, transport time, nor in time-to-imaging among patients arriving within 4 hours from symptoms onset between patients with and without a history of mental illness. Conclusions: Almost one-quarter of patients with ischemic stroke had a history of mental illness. Regardless of severity of mental illness, these patients were less likely to receive reperfusion therapy. Longer delays from symptom onset to hospital arrival contributed to the patients' risk of not being eligible for reperfusion therapy.